The Effect of Peer Observation on the Consumption of Temptation Goods: Experimental Evidence - Antonia Charlotte Grohmann; Sahra Sakha (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper uses a clean experiment to investigate the impact of peer observation on the consumption decisions of rural households in Thailand. We find that those groups that observe each other show lower within group standard deviation in their decisions. At the same time, we also find that individual choice is influenced by group choice. We find that unfamiliarity with product is counteracted by peer effects. Those in a group that have higher cognitive ability are able to resist peer temptation.
Keywords: D12; C21; D85; 330